2012
DOI: 10.1097/yct.0b013e31825cec86
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in an Adolescent With Autism and Bipolar I Disorder

Abstract: Electroconvulsive therapy should be considered a potentially useful intervention in cases of children with autistic disorder and a severe comorbid affective disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Another important consideration is suicidality, as shown by Mitchel et al 34 who found that most participants experienced both reduced suicidality and less frequent self-injurious behaviors. In some cases, bipolar disorder has been successfully treated in autistic patients 87 …”
Section: Resultsmentioning
confidence: 99%
“…Another important consideration is suicidality, as shown by Mitchel et al 34 who found that most participants experienced both reduced suicidality and less frequent self-injurious behaviors. In some cases, bipolar disorder has been successfully treated in autistic patients 87 …”
Section: Resultsmentioning
confidence: 99%
“…3,4 Electroconvulsive therapy has also been reported to be useful in patients with comorbid ID and bipolar disorder for whom compliance is an issue, as was the case with our patient. 15 Despite the evidence for the efficacy and safety of ECT in persons with ID, there remains controversy about the use of ECT in persons with ID. The primary reason may be concerns about obtaining informed consent, which may be hampered by family members who are uncomfortable about ECT.…”
Section: Discussionmentioning
confidence: 99%
“…ECT is thought to treat SIB by affecting underlying GABA dysfunction. Several case studies have reported significant reductions in drugrefractory SIB, along with mood stabilization, with ECT (Consoli et al 2013;Siegel et al 2012;Wachtel et al 2009. Studies of ECT are promising in the appropriate context as a potential treatment, and future studies will aid in defining its role in the treatment of drug-refractory SIB.…”
Section: Electroconvulsive Therapymentioning
confidence: 97%